Numerical computations – theory and algorithms : third International Conference, NUMTA 2019, Crotone, Italy, June 15-21, 2019, Revised Selected Papers.: third International Conference, NUMTA 2019, Crotone, Italy, June 15-21, 2019, Revised Selected Papers. Part II ([2020]) - Unknown
No abstract available